Problems of Transition from a Planned to a Market Economy - Wilhelm Krelle (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
The paper shows that a transition from a planned to a market economy implies an important change of the structure of production, i. e. a reallocation of resources which takes time and induces sufferings for some people. These sufferings may be reduced by subsidization of some sectors, with some negative effects on GDP and growth if subsidization exceeds a certain size. The time tillthe economy in transition reaches an ``old" market economy (asymptotically or totally) is estimated by different methods. Finally other problems, mostly non–economic ones, which are connected with the transition process are discussed.
Keywords: E1; E2; P2; 330; transition; planned economy; market economy; economic ones; which are connected with the transition process are discussed.